Paradoxical Leadership, Subjective Ambivalence, and Employee Creativity: Effects of Employee Holistic Thinking - Zhang, Yan; Zhang, Ying; Law, Kenneth S.; Zhou, Jing (Journal of Management Studies, 2022)
AbstractDrawing from meaning maintenance theory, the authors posit that paradoxical leader behaviour causes some employees to feel subjectively ambivalent, depending on holistic thinking styles. Employees who feel ambivalent will then show greater creativity as they search for ways to alleviate discomfort, again depending on thinking styles. Two field studies, one using cross‐sectional and one using panel data, confirm the hypotheses. For low (high) holistic thinkers, paradoxical leadership is more (less) positively associated with subjective ambivalence, and ambivalence is more (less) positively associated with creativity. The results offer theoretical and practical implications that holistic thinking determines whether paradoxical leadership evokes subjective ambivalence and subsequent creativity.